Impact of Fuel Cell System on Under Frequency Load Shedding Scheme Design - Jha, Rajeev; Khan, Baseem (Distributed Generation & Alternative Energy Journal, 2022)
The drop in frequency is a direct consequence of generation deficiency, either due to loss of generation or an increase in load. Therefore, in this work, to compensate for this generation deficiency following large disturbances, a fuel cell system (FCS) could be the most effective counter-measure. With the introduction of a proportional-integral (PI) controller to the FCS, the power output of the FCS can be further modified. In the present work, a two-area hydro-thermal interconnected system is being considered and simulated in MATLAB with and without FCS. From the simulation results, it is found that by using a FCS (with and without PI), the load shedding amount is reduced and the under-frequency load shedding (UFLS) scheme is made more effective.